2016
DOI: 10.3389/fgene.2016.00150
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Faba Bean Genetics and Genomics

Abstract: Vicia faba L, is a globally important grain legume whose main centers of diversity are the Fertile Crescent and Mediterranean basin. Because of its small number (six) of exceptionally large and easily observed chromosomes it became a model species for plant cytogenetics the 70s and 80s. It is somewhat ironic therefore, that the emergence of more genomically tractable model plant species such as Arabidopsis and Medicago coincided with a marked decline in genome research on the formerly favored plant cytogenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 84 publications
1
49
0
Order By: Relevance
“…Interestingly, our findings emphasize that European cultivars of the faba bean varieties minor and major do not possess a systematically different root system architecture or root morphology at maturity. This is supported by previous studies showing that both varieties are not genetically distinct (O'Sullivan & Angra, ). Although unsupervised learning has been extensively used to study plant adaptation to different environmental conditions, previous studies using UML techniques frequently failed to confirm their hypotheses (Li et al, ; Lopes et al, ; Mungomery et al, ; Wang et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, our findings emphasize that European cultivars of the faba bean varieties minor and major do not possess a systematically different root system architecture or root morphology at maturity. This is supported by previous studies showing that both varieties are not genetically distinct (O'Sullivan & Angra, ). Although unsupervised learning has been extensively used to study plant adaptation to different environmental conditions, previous studies using UML techniques frequently failed to confirm their hypotheses (Li et al, ; Lopes et al, ; Mungomery et al, ; Wang et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…We then investigated whether VC1 was able to rescue the low-vicine and convicine phenotype. In the absence of an efficient transformation method for faba bean 14 , we adopted a hairy root transformation protocol based on Agrobacterium rhizogenes 15 . We found that the ubiquitin promoter from Lotus japonicus ( pLjUbi ) 16 could successfully drive the expression of YFP in hairy roots (Fig.…”
Section: Main Textmentioning
confidence: 99%
“…Among them, Vicia faba is easy to grow with relatively high yield potential and has small number of chromosomes (2 n = 12). Thus, Vicia faba is a useful plant model for understanding the effects of various environmental factors on plants [23].…”
Section: Rosmentioning
confidence: 99%